2011
DOI: 10.1097/cji.0b013e31820e1b0d
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NKG2D-ligand Cell Surface Expression Enhances Immune Cell Therapy of Cancer

Abstract: SUMMARYA variety of immune cell therapies proposed for use in the treatment of cancer, including both autologus cells (Lymphokine Activated Killer, Cytokine Induced Killer) or cell lines (TALL-104, NK-92), rely on recognition of NKG2D ligands on malignant cells for targeting. These ligands, such as MICA and MICB in humans are stress response ligands and are commonly, but not ubiquitously expressed within tumors. Several tumor escape mechanisms have been reported, including ligand down regulation and internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
(32 reference statements)
1
51
0
2
Order By: Relevance
“…Nevertheless, through induction of natural immunity, IAP antagonists offer a promising therapeutic approach by combating two hallmarks of cancer at the same time: apoptosis resistance and evasion from immunosurveillance (Hanahan and Weinberg, 2011). Even though we report a rather small upregulation of MICA and MICB of only about 20-25%, this is likely to be of benefit in vivo, as it was recently shown that similar levels of NKG2D ligand induction were sufficient to clearly improve tumor immunosurveillance in cervical and ovarian tumors as well as melanoma mouse models (Huang et al, 2011;Pich et al, 2013). Moreover, as antibody-based tumor therapies show very promising results (Scott et al, 2012), inclu ding substances that upregulate NKG2D ligands in future trials to evaluate the possible benefit of NKG2D-mediated cancer cell killing in addition to antibody-dependent cellular cytotoxicity, should be considered.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, through induction of natural immunity, IAP antagonists offer a promising therapeutic approach by combating two hallmarks of cancer at the same time: apoptosis resistance and evasion from immunosurveillance (Hanahan and Weinberg, 2011). Even though we report a rather small upregulation of MICA and MICB of only about 20-25%, this is likely to be of benefit in vivo, as it was recently shown that similar levels of NKG2D ligand induction were sufficient to clearly improve tumor immunosurveillance in cervical and ovarian tumors as well as melanoma mouse models (Huang et al, 2011;Pich et al, 2013). Moreover, as antibody-based tumor therapies show very promising results (Scott et al, 2012), inclu ding substances that upregulate NKG2D ligands in future trials to evaluate the possible benefit of NKG2D-mediated cancer cell killing in addition to antibody-dependent cellular cytotoxicity, should be considered.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, our findings show that the combined use of MEL and marimastat enhances NK cell degranulation triggered by autologous malignant PCs. Similarly, the combination of valproate, which is known to upregulate cell surface MICA/B (25,55), and metalloproteinase inhibitors substantially stabilized cell surface MICA/B on ovarian carcinoma cells and enhanced the efficacy of immune cell therapy in vivo (56). In addition, the use of ADAM10 and ADAM17 inhibitors was shown to ameliorate the response to chemotherapy treatments in different in vivo models of cancer (57,58), and ADAM inhibitors were used in clinical trials in breast cancer patients (59).…”
Section: Discussionmentioning
confidence: 99%
“…MICA/B mRNA and membrane protein expression were up-regulated by different HDACi, e.g., Valproic acid (VPA), sodium butyrate, FR901228, Trichostatin A (TSA), suberoylanilide hydroxamic acid (SAHA), and PXD-101 in leukaemic cell lines and primary AML cells [27][28][29][30][31][32][33] and the treatment increased susceptibility to NK cells [34]. Sodium valproate and TsA reduced HDAC1 levels and enhanced histone acetylation of MICA and MICB promoters in cancer cells, augmented the expression of cell-surface NKG2D ligands, MICA/B, without increasing their soluble forms, and also increased HLA class I expression and enhanced the susceptibility to NK cell-mediated cytotoxicity [24,30,35].…”
Section: Introductionmentioning
confidence: 99%